Access Control based on Execution History - Fournet, Cédric (10th Annual Network and Distributed System Security Symposium (NDSS'03), 2003)
Security is a major, frequent concern in extensible software systems such as Java Virtual Machines and the Common Language Runtime. These systems aim to enable simple, classic applets and also, for example, distributed applications, Web services, and programmable networks, with appropriate security expectations. Accordingly, they feature elaborate constructs and mechanisms for associating rights with code, including a technique for determining the run-time rights of a piece of code as a function of the state of the execution stack. These mechanisms prevent many security holes, but they are inherently partial and they have proved difficult to use reliably. We motivate and describe a new model for assigning rights to code: in short, the run-time rights of a piece of code are determined by examining the attributes of any pieces of code that have run (including their origins) and any explicit requests to augment rights. This history based model addresses security concerns while avoiding pitfalls. We analyze the model in detail; in particular, we discuss its relation to the stack-based model and to the policies and mechanisms of underlying operating systems, and we consider implementation techniques. In support of the model, we also introduce and implement high-level constructs for security, which should be incorporated in libraries or (even better) in programming languages.